Resilient and Sensitive Key Points of the Photosynthetic Machinery of Coffea spp. to the Single and Superimposed Exposure to Severe Drought and Heat Stresses - Dubberstein, Danielly (2021)
No 727934 PTDC/ASP-AGR/31257/2017 UIDB/00239/2020 UIDP/04035/2020 E-26/202.323/2017